REGIONAL DYNAMICS OF PRIVATE PENSION FUNDS IN ROMANIA - Dan Constantinescu (European Regional Science Association (ERSA), 2011)
The number of participants in the private pension funds, as well as the volume of their contribution, differs significant in each development region. It goes without saying that the territorial distribution of the indicators related to pension funds are influenced, on the one hand, by the offer of these financial products, which we estimate counting the number of marketing agents authorized by the supervisory committee and, on the other hand, by the solvent demand, which is also determined by a series of economic, social, cultural and institutional. Since the emergence of pension funds in Romania is relatively new, for developing the econometric model we had to use monthly data series, which has induced a number of restrictions related to the information available in this format. Also, to increase the model's number of degrees of freedom, the data on the indicators will be detailed in the 42 counties, local structures corresponding to NUTS-III level.
Keywords: 330